Land Use Changes of Pohorske Planje between 2000 and 2014 - Golob, Tanja; Kodrič, Domen; Meolic, Jelko; Praprotnik, Aleš; Premužič, Aleksandra; Simreich, Anja; Viltužnik, Rosvita (Journal for Geography, 2015)
The article treats natural characteristics of Pohorske Planje area and the changes in cultural landscape because of land use. The natural characteristics are analysed and shown on the evidence of land categories. The changes in land categories from the year 2000 to 2014 are also shown. The analysis shows a change in cultural landscape. The changes can be seen in expansion of forest and in extensification of agricultural areas.
Keywords: Pohorje; Pohorske planje; cultural landscape; land use; physical geography; geographical information system